Plant growth-promoting endophytic bacteria isolated from Launaea arborescens (characterization and molecular identification) - Mebarki Lakhdar; Dakhali Abir; Mezouri Fatna (Future Science, 2023)
The present investigation aimed to assess endophytic bacteria's capacity to stimulate plant development. Eight endophytic bacterial strains were isolated from the root of Launaea arborescens (Batt.), native medicinal plant growing spontaneously in the region of Bechar (south-west Algeria). The eight strains were tested for their effects on seed germination and plant growth of Triticum aestivum L. The results showed that all strains had positive effects on wheat seeds germination. The seeds inoculation of wheat by endophytic bacteria improves morphological parameters of the seedling (fresh and dry weight of plant, root and stem elongation). 16S rRNA gene sequencing was used to identify the powerful strain, it was found as Brevibacillus brevis. This one was found positive for many of the plant growth promoting attributes like ammonia production and azote fixing. In addition, it was identified as resistant to azithromycine during antibiotic sensitivity test and It could tolerate up to 0.9 M of NaCl. Additionally, Brevibacillus brevis was identified as resistant in the herbicide and the insecticide susceptibility test. Results suggest that this endophyte is a strong candidate for use as plant growth-promoting inoculants, to assist in lowering the amount of chemicals used in agricultural practices and enhance nutrient absorption and stress resistance in plant species.